Специфіка функціонування підприємств аграрного сектору у контексті соціально-економічного розвитку України - Поленкова, М. В.; Polenkova, M. (ЦНТУ, 2020)
В статті обґрунтовано вагому роль сільського господарства в економічній системі України. Виявлено ключові тенденції функціонування підприємств аграрного сектору України. Досліджено динаміку обсягів виробництва сільськогосподарської продукції. Окреслено послідовність застосування методу багатофакторного динамічного регресійного моделювання. В рамках дослідження розраховано вплив функціонування підприємств аграрного сектору на індекс виробництва сільськогосподарської продукції. The article substantiates the important role of agriculture in the economic system of Ukraine. The key tendencies of functioning of the enterprises of the agrarian sector of Ukraine are revealed. The dynamics of agricultural production volumes is studied. The sequence of application of the method of multifactor dynamic regression modeling is outlined. The study calculated the impact of the functioning of agricultural enterprises on the index of agricultural production. Improving the competitiveness of the national agricultural sector involves the sustainable operation of all its interconnected subsystems: agro-industrial production; food markets; sale, distribution and consumption of food; personnel, financial, logistical, technological, informational and scientific support. However, in modern conditions, the functioning of agricultural enterprises is accompanied by a number of problematic aspects, which significantly hinders their long-term development. In the context of European integration there is an objective need to form effective mechanisms to strengthen the competitive position of Ukrainian. The agricultural sector plays a strategic role in the socio-economic development of the country. The increase in agricultural production and the growth of per capita income of the rural population together with industrialization and urbanization lead to an increase in demand for industrial production. According to the results of the calculations based on the balance cross-section regression, the indicators of functioning of agricultural enterprises that have the greatest impact on the index of agricultural production are identified. According to the results of the analysis, the greatest influence among the studied indicators on the index of agricultural production is noted: the volume of production of roots, tubers, crops of vegetables and melons by food farms of all categories; volumes of production of technical crops by enterprises; costs of enterprises for fuel and lubricants. Significant positive impact is also exerted by the area from which enterprises harvested cereals and legumes and the yield of cereals and legumes at enterprises. В статье обоснована важная роль сельского хозяйства в экономической системе Украины. Выявлены ключевые тенденции функционирования предприятий аграрного сектора Украины. Исследована динамика объемов производства сельскохозяйственной продукции. Определены последовательность применения метода многофакторного динамического регрессионного моделирования. В рамках исследования рассчитано влияние функционирования предприятий аграрного сектора на индекс производства сельскохозяйственной продукции.
Specifics of the Functioning of Agricultural Enterprises in the Context of Socioeconomic Development of Ukraine
Специфика функционирования предприятий аграрного сектора в контексте социально-экономического развития Украины
Keywords: продукція рослинництва; продукція тваринництва; сільськогосподарські підприємства; аграрний сектор; соціально-економічний розвиток; crop products; livestock products; agricultural enterprises; agricultural sector; socio-economic development; продукция растениеводства; продукция животноводства; сельскохозяйственные предприятия; аграрный сектор; социально-экономическое развитие